Unusual features in the conjunctiva and cornea of the normal guinea-pig: clinical and histological studies. - Dwyer, R S (1983)
Clinical and histological studies of the outer eyes of newborn and adult female guinea-pigs were carried out together with histological studies of fetal eyes. Fine superficial corneal vessels, extending from the limbus, were seen in most newborn and adult eyes and were also present in histological preparations of fetal eyes. These vessels were therefore considered to be features of the normal guinea-pig eye. Masses of tissue composed of lymphoid cells, which were often organised into germinal centres, were found in the fornices of newborn and adult eyes. Smaller accumulations of lymphoid cells were found in fetal eyes, and this lymphoid tissue was therefore also considered to be a normal feature of the guinea-pig eye. In adult eyes mild but short-lived oedema or hyperaemia of the palpebral conjunctiva was quite common. There were no differences in the amounts of conjunctival cellular infiltration in these eyes c found in fetal eyes, and this lymphoid tissue was therefore also considered to be a normal feature of the guinea-pig eye. In adult eyes mild but short-lived oedema or hyperaemia of the palpebral conjunctiva was quite common. There were no differences in the amounts of conjunctival cellular infiltration in these eyes c found in fetal eyes, and this lymphoid tissue was therefore also considered to be a normal feature of the guinea-pig eye. In adult eyes mild but short-lived oedema or hyperaemia of the palpebral conjunctiva was quite common. There were no differences in the amounts of conjunctival cellular infiltration in these eyes compared with normal eyes, and these inflammatory changes were therefore not considered to be significant.